Letter (copy) : Help for the Workers of Spain Fund - Tewson, Vincent
1937-01-06 Our Ref: HVT/FC/EK/286. 6th January, 1937. Mr. E. Lynch, The Irish Trade Union Congress, Rooms 34 and 35, 32, Nassau Street, DUBLIN, C.2. Dear Mr. Lynch, HELP FOR THE WORKERS OF SPAIN FUND. I have your letter of the 21st December in regard to the above matter and in reply I may say that the Fund in this country was initiated by the National Council of Labour immediately after the outbreak of hostilities. A few days afterwards there was a joint meeting of the International Federation of Trade Unions and the Labour and Socialist International who decided to issue an international appeal and our Fund is part of the International Fund. I think that answers your question as to who initiated the Fund. In regard to the purpose of the Fund this is purely for relief work and large quantities of medical supplies, food and clothing are continually being sent to Spain. 292/946/28/118(i)